Historiographical Approaches on Experience and Empiricism in the Early Nineteenth-Century: Degérando and Tennemann - Manzo, Silvia (2019)
This paper examines the views of Joseph-Márie Degérando and Wilhelm Gottlieb Tennemann about empiricism, and the scope and limits of experience as well as its relation to reason and its role in the attainment of true knowledge. While Degérando adopted the "philosophy of experience" and Tennemann advocated Kant's critical philosophy, both authors blamed each other for the same mistake: if Degérando considered that, despite all appearances to the contrary, critical philosophy fell into empiricism, Tennemann judged that the philosophy of experience was nothing but pure and simple empiricism. Degérando's and Tennemann's discrepancies involved not only a discussion of "nomenclatures" and of the role and limits of experience in knowing, but also an epistemological and ideological commitment to the pacification of the intellectual field in the aftermath of the French Revolution. In this line, Degérando's alignment with the philosophy of experience attempted to distance himself from the politically dangerous sensualism attributed to the idéologie. But, unlike his countryman Charles Villers, he did not want to replace the sensualism by critical philosophy. His opposition to philosophical novelty (which he associated with political revolution) led him to praise only the "eclectic" spirit of Kant's philosophy.